O15.2 Interested? why or why not? STI clinic client perceptions of bacterial STI vaccines in british columbia, canada. (14th July 2019) - Plotnikoff, Kara; Ogilvie, Gina; Smith, Laurie; Pedersen, Heather; Donken, Robine; Samji, Hasina; Grennan, Troy
Abstract : Background: Sexually transmitted infections (STIs) contribute to a large global health burden, potentially leading to cancer, infertility, and increased risk of contracting other STIs. Several STI vaccines are in development, with the potential to decrease STI prevalence and morbidity. However, concerns remain regarding acceptability across populations. To plan for implementation and rollout, the objective of this study was to explore attitudes STI clinic clients have towards STI vaccines, including acceptability and perceived barriers. Methods: The STRIVE-BC consortium - a group of public health leaders, scientists, and clinicians focused on STI vaccine research - implemented a 31-item questionnaire at two large STI clinics in Vancouver, Canada to understand STI vaccine acceptability. Demographic and clinical characteristics were summarized using descriptive measures. A multivariable logistic regression (MLR) model was constructed using a combination of a priori clinically relevant variables and significant covariates ( p ≤ 0.05) from univariate analysis. The MLR model assessed predicting factors of STI vaccine interest as odds ratios (ORs) with 95% confidence intervals (CI). Results: 293 surveys were analyzed with 86.5% of respondents reporting they would be interested in receiving an STI vaccine. The average respondent was a 33-year-old Caucasian heterosexual male with post-secondary education. MLR indicated that willingness to pay was a significant factor for syphilis vaccine interest (OR=3.83, 95% CI=1.29, 11.38, p =0.02). Intent to engage in positive health behaviours after vaccination was significant for chlamydia (OR=5.94, 95% CI=1.56, 22.60, p =0.01) and gonorrhea (OR=5.13, 95% CI=1.45, 18.07, p =0.01) vaccine interest. Conclusion: Participants attending large STI clinics expressed a strong willingness to receive STI vaccines. As STI vaccines are still years away from commercial availability, highlighting acceptable cost, ages, and anticipated health behaviours allows for informed implementation and rollout. Research priorities and areas of future work including additional populations and explorations of hesitation can be considered by attendees to apply within their research and practice areas. Disclosure: No significant relationships.